Literasi Digital Pada Aspek Hukum Bisnis UMKM Kelompok Usaha PKK Desa Wisata Pulau Pahawang - Dwi Nurahman; Yulistina Yulistina; Yodhi Yuniarthe; Resy Anggun Sari; Dina Haryati (BADAN PENERBIT STIEPARI PRESS, 2023)
Lampung Province is a province located at the tip of the island of Sumatra which is the gateway between the islands of Java and Sumatra. Lampung is a province that has a variety of tourist destinations, especially coastal and island tourism which has beautiful panoramas and a wide variety of interesting marine habitats for tourists to visit, both local, national and international. One of the island's tourist destinations that is interesting and has good potential, namely the tourist village on Pahawang Island, apart from offering beautiful beaches and interesting marine habitats to visit, the people of Pahawang Tourism Village have potential in the field of MSME Business, especially PKK women and Karang Taruna youth like making Dodol. For this reason, it is hoped that the participation of universities to provide a legal basis for MSMEs is contained in Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises (UU.UMKM).